Heurística para programação de tabelas de competições esportivas e sua aplicação ao campeonato nacional de basquete - Pavan, Marcus Vinicius de Souza (2006)
scheduling of sport leagues has become an important class of combinatorial optimization problems in recent years. Numerous professional sport leagues deal with this problem in every season. There are important issues that have to be considered in the scheduling, besides traditional requirements like the distance that teams need to travel. Different techniques have been used to solve this kind of problem. In this work, we propose a heuristic for sports scheduling problems and apply it to the 2004 edition of the men s Brazilian Basketball Tournament. Computational experiments are performed and the results obtained by the heuristic are compared with those published by Confederação Brasileira de Basquete to assess the effectiveness of the proposed solution strategy.